Understanding Respiratory Syncytial Virus Infection to Improve Treatment and Immunity - A. Gonzalez, P.; J. Carreno, L.; M. Bueno, S.; A. Riedel, C.; M. Kalergis, A. (Current Molecular Medicine, 2013)
Despite significant research since it was discovered more than 50 years ago, respiratory syncytial virus (RSV) continues to be the leading agent causing infant hospitalization and respiratory distress worldwide. Although RSV normally does not cause mortality, this virus is recognized as a major public health and economic burden around the globe. RSV can modulate host immunity leading to an inflammatory response that produces lung damage and virus dissemination in the host airways. Remarkably, infection with the virus elicits poor immunity that in most cases fails to protect against subsequent exposures. Here, we review advances made on the understanding of the lifecycle of the virus, some of the molecular mechanisms it has evolved to cause pathology and ineffective immunity during infection. Hopefully, ongoing research will contribute to developing new drugs and candidate vaccines that will decrease the health burden caused by this virus.
Keywords: immune modulation